(3cJGH GdeYhfI aj Yde GdMSGH GdghGFis - (3CMeO Hf eMeO Hf YeGO GdOjf Hf Ydj GdefUhQj GdSdej, GHf GdgGFe,TgGH GdOjf, J (B815 (3g` s ((3eMeO Hf eUWai GdTgjQ HGdWfWGhi s)
(3ChdgG (B:s
(3GdMeO ddg Ydi YOO fYeGFg CeG HYO agPg QSGdi ai Yde GdMSGH bO CdaJgG dHYV GdCNhGf GdebOeI ajgG eSGFd GdChdi ai JYQja GdMSGH s
(3BNQgG (B:s
(3aGLeY LejY GdLed hGbSe eLehYgG Ydi YOI MQha GdGSe GdeVeQ GdGhGMOkG aeG NQO agh LedI MQha GdGSe gPG BNQ GdeYhfI s
(3HgG fXGe GdJYbjHIs
(3HBNQgG aGFOI ai GdMSGH Hbde eMeO eUWai GdTgjQ HGdWfWGhis
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B226s
Keywords: (3GdQjGVjGJs